Organizational Trust Between Institutional and Interpersonal Trust - Rusu Raluca; Baboş Alexandru (Scientific Bulletin, 2015)
This paper presents organizational trust as antecedent for organizational effectiveness. The main discussed problem, after trust perspectives interpretation presentation (rational and identification), is linked to the way in which trust can be built in organizations by managers, starting from managing the interpersonal trust.